Using the HFMEA tool to improve pressure injury risk management in intensive care patients - Araujo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra; Souza, Itayany de Santana Jesus (Brazilian Journal of Production Engineering, 2024)
The search for management that actively integrates aspects of quality, health, safety and the environment in health systems has brought about the need to identify and prevent potential failures. Therefore, the present research aims to investigate the possible failure modes and effect of Pressure Injury (PPI) in patients in the Intensive Care Unit (ICU) of a public hospital, through the application of the HFMEA method. The research is characterized as exploratory and descriptive of the case study type, making it possible to obtain in its results the establishment of improvement actions for those failure modes that presented RPN greater than 630, which mainly refer to training and continuing education programs. Furthermore, the tool proved to be necessary for hospital risk management.
Keywords: HFMEA; Risk management; safety